FAKTOR DETERMINAN KEJADIAN ANEMIA PADA IBU HAMIL TRIMESTER III - Apriliana, Mia; Tampubolon, Rifatolistia; Mangalik, Gelora (Care : Jurnal Ilmiah Ilmu Kesehatan, 2022)
The incidence of anemia in pregnant women in Indonesia was 48,9% in 2018 up from 37,1% in 2013. The number of pregnant women with anemia at the Ketapang I Sampit Community Health Center in Central Kalimantan increased to 150 in 112 in 2017. The research aimed to describe the determinants factor of anemia in Trimester III pregnant women at the Ketapang I Sampit Community Health Center in Central Kalimantan. This research used descriptive quantitative methods with a cross-sectional approach. A total of 31 respondents were sampled using the purposive sampling technique. The research data are tabulated before being describe. The findings revealed that pregnant women with anemia were between the ages 20-35 years old (71%), had completed high school (52%), nullipara (45%), had a two-year gap between pregnancies (29%), not working (75%), low income (58%), did not take blood-booster tablets (84%), pregnant women who do not make a pregnancy visit in the Trimester I (81%) and the most commonly consumed food  pregnant women is rice, chicken eggs, tofu, spinach and mangoes. This research concluded that the determinants factors in the incidence of anemia in pregnant women were parity, birth spacing, occupation, income, adherence to blood-booster intake and pregnancy frequency.